Flexible societies excelled in saving lives in the first phase of the COVID-19 pandemic - Li, Jianghong; Akaliyski, Plamen; Heisig, Jan Paul; Löbl, Simon; Minkov, Michael (Frontiers in Psychology, 2022)
Previous studies have shown that national cultural traits, such as collectivism-individualism and tightness-looseness are associated with COVID infection and mortality rates. However, no studies to date have examined flexibility-monumentalism, a cultural trait that uniquely distinguishes East Asia from the rest of the world. East Asian countries have out-performed other countries in containing COVID infections and lowering mortality in the first pandemic waves. Moreover, none of the previous studies have explored mechanisms underpinning the association between national culture and COVID mortality. Our study fills in these gaps by examining the association between flexibility-monumentalism and COVID-19 mortality in 37 countries, adjusting for important covariates and by analyzing plausible mechanisms underpinning this association. The results show that flexibility is associated with a significant reduction in COVID-19 mortality as of 31 October 2020, independent of the level of democracy, per capita GDP, urbanization, population density and hospital beds. This association is also independent of two other prominent national cultural traits (individualism-collectivism and tightness-looseness) which have received much attention. We also found tentative evidence that the flexibility- COVID mortality is mediated through mask wearing.